Unit commitment with AC power flow constraints for a hybrid transmission grid - Sampath, Lahanda Purage Mohasha Isuru (2019)
A unit commitment formulation satisfying AC optimal power flow constraints models the resource optimization problem accurately, but is challenging to solve for traditional transmission systems. Integration of generation based on renewable energy sources is often limited by transmission congestion issues in existing grids. For such grids, AC to HVDC conversion schemes are viable and attractive options for capacity expansion. In this respect, we utilize the structural properties of a hybrid AC/HVDC grid architecture with a specific topology to enable an exact mixed integer conic relaxation of the aforementioned problem. The simulation results for the PJM 5-bus system show that the relaxation is exact for the hybrid architecture. Further, it alleviates the network congestion leading to a substantial reduction in generation cost at normal and increased load conditions compared to the reference AC grid. Moreover, the hybrid architecture improves the utilization of the grid to accommodate more demand and generation.